Current trends and future perspectives of natural polymer loaded nanoparticle based drug delivery system for the management of inflammatory bowel disease - Basak, Ankita; Ghosh, Soumyadip; Ganguly, Debgopal; Garain, Soukat; Ghosh, Riya; Choudhury, Ananta; Deka, Himangshu; Sarmah, Jahnabi (Creative Pharma Assent, 2023)
Targeting the drug delivery system is very tough nowadays due to premature drug release at the upper GIT tract and altered pH conditions. Colon-specific drug delivery systems can overcome that problem using different polymer combinations. A nanoparticulate drug delivery system is the prominent dosage form that impacts the bioavailability and requires a low dose to excrete the therapeutic efficacy. All nanoscience and nanotechnology are applications of Nanometrology, the science of measurements at the nanoscale. NPDDSs were primarily developed to combine the colloidal stability of solid particle suspensions in biological fluids and the solubilizing properties of liquids. An ideal drug-delivery system possesses two elements: the ability to target and control the drug release. Colloidal drug carriers offer a number of potential advantages as delivery systems, such as better bioavailability for poorly soluble drugs. Researchers have created various sophisticated and multifunctional nanocarrier systems that can transport pharmaceuticals in a targeted, sustained, and regulated manner to provide therapeutic medications that are safer and more effective, particularly to ulcerative colitis. These innovative technologies are improving the pharmacokinetic profile of pharmaceuticals, increasing their systemic circulation, and decreasing the frequency of pharmacological side effects. The review focuses on the current trend and future perspectives of natural polymer-based-loaded nanoparticle-based drug delivery systems for the management of inflammatory bowel disease.